2022
DOI: 10.3390/biomedicines10112995
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Identification of Genes Associated with Breast Cancer Progression and Prognosis and Novel Therapeutic Targets

Abstract: Molecular mechanisms underlying breast cancer (BC) progression are complex and remain unclear. In this study, we used bioinformatic tools to identify genes associated with tumor progression mechanisms and novel therapeutic targets in BC. We identified genes with stepwise upregulated expression overlapping between the T and N stages during BC progression using LinkedOmics. We compared the expression level of each gene in BC tissues with that in normal breast tissues and evaluated differences in expression in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Disease development is also influenced by a number of other factors, such as environmental and lifestyle impacts (Criscitiello and Corti 2022). There are several other genes known to be involved in breast cancer progression like TRIM3, ABCB9, SPDEF, HSPB1, RHBG, SPINT1, EPN3, LRFN2, PRPH, etc (Uchida et al 2022). SPDEF (Sam pointed domain containing ETS transcription factor) is a prostate-derived ETS factor that maintains homeostasis, and differentiation of epithelial tissues, and heritable alterations in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Disease development is also influenced by a number of other factors, such as environmental and lifestyle impacts (Criscitiello and Corti 2022). There are several other genes known to be involved in breast cancer progression like TRIM3, ABCB9, SPDEF, HSPB1, RHBG, SPINT1, EPN3, LRFN2, PRPH, etc (Uchida et al 2022). SPDEF (Sam pointed domain containing ETS transcription factor) is a prostate-derived ETS factor that maintains homeostasis, and differentiation of epithelial tissues, and heritable alterations in cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Next, Kawashita et al revealed that the degree of radiation-induced mucositis can be predicted on the basis of patient lymphocyte counts at the pre-radiation stage [5]. Other studies focusing on individual cancer types are included in this Special Edition, with research on breast cancer [6], renal cell carcinoma [7,8], ovarian cancer from ovarian endometrioma [9], and inflammatory bowel disease (IBD), conditions which sometimes transform into cancer-prone phenotype [10]. Breast cancer is the most commonly diagnosed cancer in women, and Uchida et al identified the nine candidate genes constituting therapeutic targets of breast cancer using existing databases.…”
mentioning
confidence: 99%
“…Breast cancer is the most commonly diagnosed cancer in women, and Uchida et al identified the nine candidate genes constituting therapeutic targets of breast cancer using existing databases. These were RNA-seq-based expression profiles taken from breast cancer tissues and CRISPR-Cas9/RNAi-based dependency maps of genes based upon the survival rate of cell lines derived from breast cancer tissue [6]. Clear cell renal cell carcinoma (ccRCC) is dominant in kidney cancer, the mortality rate for which has recently increased worldwide.…”
mentioning
confidence: 99%